Disturbing Femininity - Kirsten Hvenegård-Lassen (Culture Unbound: Journal of Current Cultural Research, 2013)
When Helle Thorning-Schmidt in 2011 became the first female Prime Minister in Denmark, this “victory for the women” was praised in highly celebratory tones in Danish newspapers. The celebration involved a paradoxical representation of gen-der as simultaneously irrelevant to politics and – when it comes to femininity – in need of management. Based on an analysis of the newspaper coverage of the elec-tion, I argue that highlighting gender (in)equality as either an important political issue or as something that conditions the possibilities of taking up a position as politician was evaluated as a performative speech act, i.e. an act that creates the trouble it names. Ruling out gender equality as relevant was, however, continually interrupted by comments on how Thorning-Schmidt and other female politicians perform gender in ways that fit or do not fit with “doing politician”. These com-ments tended to concern the styling of bodies and behaviour and followed well known – or sticky – gendered scripts.